2014
DOI: 10.1039/c4ra09552a
|View full text |Cite
|
Sign up to set email alerts
|

Pectin cross-linked enzyme aggregates (pectin-CLEAs) of glucoamylase

Abstract: 1Pectin cross-linked enzyme aggregates (pectin-CLEAs) of glucoamylase were prepared for 2 the first time with pectin as cross-linking agent. Pectin as biocompatible, biodegradable, non-3 toxic, renewable and macromolecular cross-linker was used instead of traditional micro-4 molecular glutaraldehyde cross-linker. Cross-linker was prepared by controlled sodium 5 metaperiodate oxidation of native pectin. The effects of precipitant type, amount of 6 precipitant and cross-linking on activity recovery of glucoamyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The changes in fractions of secondary structure of free glucoamylase and hybrid glucoamylase nanoflowers were estimated by using FT-IR method according to the previous literature [23]. The FT-IR spectra of free and immobilized glucoamylase were recorded using Shimadzu IRAffinity-1 FT-IR spectrophotometer from 4000 to 400 cm -1 with sample dispersed in the KBr pellets.…”
Section: Secondary Structure Analysis By Ft-ir Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in fractions of secondary structure of free glucoamylase and hybrid glucoamylase nanoflowers were estimated by using FT-IR method according to the previous literature [23]. The FT-IR spectra of free and immobilized glucoamylase were recorded using Shimadzu IRAffinity-1 FT-IR spectrophotometer from 4000 to 400 cm -1 with sample dispersed in the KBr pellets.…”
Section: Secondary Structure Analysis By Ft-ir Methodsmentioning
confidence: 99%
“…The second derivative FT-IR spectra for free glucoamylase and hybrid nanoflowers were obtained ( Figure S1-2 †).The relative contents of α-helix structure (1650-1658 cm -1 ) (blue), β-sheet structure (1610-1640 cm -1 ) (red), β-turn structure (1660-1700 cm -1 ) (yellow) and random coil structure (1640-1650 cm -1 ) (green) based on the modelled multi-component peak areas calculated according to the previous literature by the software (Figure 6a-b) [23][24].…”
Section: Secondary Structure Analysis Of Free Glucoamylase and Hybridmentioning
confidence: 99%
“…Moreover, there is a need to select the best promising polysaccharide for conjugation with the desired enzyme, as the enzyme interacts in different ways with different polysaccharides [16]. All the polysaccharides used considerably increased the thermal stability of cutinase ( Fig.1) A c c e p t e d M a n u s c r i p t 12 stabilize the glucoamylase [19]. Li et al [15] also observed different thermostability for β-Dglucuronidase with similar molecular structural polysaccharides with different charges.…”
Section: Screening Of Polysaccharides For Non-covalent Interaction Wimentioning
confidence: 98%
“…Further, conjugation of glucose oxidase and horseradish peroxidase with dextran [13], β-glucuronidase to polysaccharides [15], alcohol dehydrogenase with dextran and gum Arabic [14] enhanced thermal and pH stability. Pectin has been previously reported not only Page 5 of 52 A c c e p t e d M a n u s c r i p t 5 to have a prominent role in aggregation of glucoamylase and folding but also increase its thermal stability and reusability [19].…”
Section: Introductionmentioning
confidence: 99%
“…The process of CLEAs formation involves the treatment of enzymes immobilized on supports that are non-reactive to glutaraldehyde in order to prevent enzyme leakage followed by the crosslinking of enzymes adsorbed on aminated supports. This method was used to prepare CLEAs of trehalose synthase via co-aggregation with polyethyleneimine 11 and pectin CLEAs of glucoamylase 12 . Thus, glutaraldehyde remains the most widely used compound for designing biocatalysts to be utilized in a large number of biomedical and biotechnological applications.…”
Section: Fig 1: Chemical Properties Of Glutaraldehydementioning
confidence: 99%